Meaning of Yukie Chiri & Ainu's Manga Cultural Vocabulary as an Entrance to Japanese Ainu Cross-Cultural Understanding - Ida Ayu Laksmita Sari; Ni Luh Kade Yuliani Giri (Institut Pariwisata dan Bisnis Internasional, 2026)
This study examined the cultural vocabulary contained in Yukie Chiri & Ainu's manga (comic) (2017). Yukie Chiri & Ainu manga is a comic that tells the journey of a girl named Yukie Chiri in collecting Ainu folklore. Using ethnographic semantic theory, this study focused on the identification, categorization, and meaning of the Ainu cultural system through vocabulary related to cultural elements used in the Yukie Chiri & Ainu manga. The study results show several cultural vocabularies used to introduce Japanese Ainu culture, namely the vocabulary of belief systems, types of rituals, ritual means, place names, seasons, and living equipment of the Ainu people. This study contributes to the understanding that this manga not only introduces narratives and forms of folklore such as yukar as cultural heritage but also confirms that this manga also introduces Ainu cultural vocabulary which is the entry point for readers for cross-cultural introductions.